Wage inequality, skills and mastering new technologies (2017)
In this paper I provide a new explanation for the raising inequality between skilled and unskilled. Unlike the skilled biased technological change explanation, I do not assume that new technologies are necessarily complementary with skills. Instead, the adoption of new technologies have mastering costs that have a inverse relation with skills. Thus, skilled individuals master new technologies faster than unskilled individuals which gives them edge apart from being more skilled. The model predicts changes in the distribution of wages in favor mainly of agents in the tails of the distribution. As a result, the gap between skilled and unskilled increases and the general levels of inequality of the economy also rises.